Interventions against Aedes/dengue at the household level: a systematic review and meta-analysis - Montenegro Quiñonez, Carlos Alberto; Louis, Valérie R.; Horstick, Olaf; Velayudhan, Raman; Dambach, Peter; Runge-Ranzinger, Silvia (EBioMedicine, 2023)
Background - Because the evidence for the role of structural housing and combinations of interventions (domestic or peri-domestic) against Aedes mosquitoes or dengue is still lacking, this systematic review and meta-analysis aimed to analyse and synthesize research focusing on the household as the unit of allocation. - Methods - We searched MEDLINE, LILACS, and Web of Science databases until February 2023 using three general keyword categories: (1) “Aedes” or “dengue”; (2) structural housing interventions including “house”, “water”, or “drainage”; and (3) vector control interventions of potential relevance and their combinations. We performed a qualitative content analysis and a meta-analysis for 13 entries on dengue seroconversion data. - Findings - 14,272 articles were screened by titles, 615 by abstracts, 79 by full-text. 61 were selected. Satisfactory data quality allowed for detailed content analysis. Interventions at the household level against the immature mosquito stages (21 studies, 34%) showed positive or mixed results in entomological and epidemiological outcomes (86% and 75% respectively). Combined interventions against immature and adult stages (11 studies, 18%) performed similarly (91% and 67%) while those against the adult mosquitoes (29 studies, 48%) performed less well (79%, 22%). A meta-analysis on seroconversion outcomes showed a not-statistically significant reduction for interventions (log odds-ratio: −0.18 [−0.51, 0.14 95% CI]). - Interpretation - No basic research on housing structure or modification was eligible for this systematic review but many interventions with clear impact on vector indices and, to a lesser extent, on dengue were described. The small and not-statistically significant effect size of the meta-analysis highlights the difficulty of proving effectiveness against this highly-clustered disease and of overcoming practical implementation obstacles (e.g. efficacy loss, compliance). The long-term success of interventions depends on suitability, community commitment and official support and promotion. The choice of a specific vector control package needs to take all these context-specific aspects into consideration. - Funding - This work was funded by a grant from the World Health Organization (2021/1121668-0, PO 202678425, NTD/VVE).